Analisis Ancaman Banjir pada Sistem Drainase Banger Lama, Kota Pekalongan: Pengaruh Faktor Hujan, Kenaikan Muka Laut, dan Penurunan Tanah - Huseiny, Mohammad Iqbal; Kuntoro, Arno Adi; Nugroho, Eka Oktariyanto; Farid, Mohammad; Nurmaulia, Sella Lestari (Jurnal Teknik Sipil, 2024)
Abstract The coastal areas of Pekalongan City face a significant threat due to flooding and tidal surges. The low, flat topography complicates the management of drainage systems, given the relatively gentle land slope. Flooding incidents frequently occur in various parts of Pekalongan City. Furthermore, the global rise in sea levels and land subsidence in the region exacerbate this issue. This study aims to model the drainage system, considering factors such as rainfall, sea level rise, and land subsidence in Pekalongan City. The modeling is conducted by integrating 2D and 1D models using the Personal Computer Storm Water Management Model (PCSWMM) software. The modeling results encompass three parameters: flood depth, flood velocity, and flood duration. Subsequently, a flood hazard map is developed based on the Flood Hazard Index, incorporating these three parameters. Recommendations to address this issue include constructing embankments and flap gates upstream in flood-affected areas, as well as modifying the drainage system to enable gravity-driven water flow downstream without the use of pumps. However, it is essential to note that these recommendations may not be effective in scenarios involving significant land subsidence. This research is anticipated to assist stakeholders in making informed decisions regarding the management of the drainage system in Pekalongan City. Keywords: Drainage, PCSWMM, flood, sea level rise, land subsidence